Trollflöjten = The magic flute [videorecording (DVD)] - Zollo, Carmen F.; Bergman, Ingmar, 1918-2007; Bergman, Ingmar, 1918-2007; Bergman, Ingmar, 1918-2007; Cold, Ulrik; Köstlinger, Josef; Sædén, Erik; Nordin, Birgit, 1934-2022; Urrila, Irma; Hagegård, Håkan; Ericson, Eric, 1918-2013; Nykvist, Sven; et al. (Criterion collection, 2000)
An opera by Mozart, in which a handsome young man is enlisted to rescue the Queen of Night's daughter from an evil sorcerer.